The History of Diabetes Mellitus - Rehan Haider; Asghar Mehdi (International Journal of Scientific Multidisciplinary Research, 2023)
Diabetes mellitus, an incessant metabolic disorder caused by increased blood glucose levels, has a rich and complex history spanning paradise. The first famous reference to diabetes dates back to ancient Egypt, where the condition was defined in healing texts around 1500 BCE. However, it was not just before the 19th century that important progress had been made in understanding and directing diabetes. In 1889, two German physicians, Joseph von Mering, and Oskar Minkowski, fashioned an important finding by professing that the removal of organ meat in dogs caused diabetes-like manifestations. This led to the identification of organ meat as an insulin source. In 1921, a Canadian group led by Frederick Banting and Charles Best released insulin, a birth control method that is critical for regulating glucose levels. This finding was obvious at a critical juncture in diabetes administration, as insulin injections have become a lifesaving situation for things associated with type 1 diabetes